The basics of cyber warfare understanding the fundamentals of cyber warfare in theory and practice - Winterfeld, Steve (Syngress/Elsevier, 2013)
Provides readers with fundamental knowledge of cyber war in both theoretical and practical aspects. This book explores the principles of cyber warfare, including military and cyber doctrine, social engineering, and offensive and defensive tools, tactics and procedures, including computer network exploitation (CNE), attack (CNA) and defense (CND).